On moment maps and Jacobi manifolds (2021)
The main goal of this work is to introduce the idea of a Hamiltonian action in the context of Jacobi structures on line bundles. This work aims to make these construction without relying on the "Poissonization trick". Our definition allows us to recover the notion of (weakly)Hamiltonian action in the context of Poisson, contact, and locally conformally symplectic geometry.